The Power of Asset Mapping: How Your Congregation Can Act on Its Gifts - Snow, Luther K., (Rowman & Littlefield Publishers, 2004)
Asset mapping isn't a new system or theory. It's a way of thinking, a doorway into an "open-sum" perspective rooted in the Bible and common experience. The Power of Asset Mapping, by long-time community developer Luther K. Snow, shows congregational leaders how to help a group recognize its assets and the abundance of God's gifts and to act on them in ministry and mission. Congregations will find the book easy to read and immediately useful. Leaders can begin with the tested Quick and Simple Asset Mapping Experience to strengthen and inspire any group in the congregation in as little as an hour. Futher tips, techniques, stories, and lessons drawn from the experience of diverse congregations will help readers discover how asset mapping works. Finally, Snow provides lessons about why asset mapping strengthens faith and community.